Hadith #2114 - Sahih Muslim - Mas'ud bin Jwyryh bin Da'ud مسعود بن جويرية بن داود (Sahih Muslim)
Verily, the Prophet (ﷺ) used to stand first but later on kept sitting; but it is also narrated that Nafi’ ibn Jubair saw Waqid b. ‘Amr standing for a bier till it was placed down.
Grade: Sahih